2011
DOI: 10.1158/0008-5472.can-10-2012
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of H2AX at Ser139 and a New Phosphorylation Site Ser16 by RSK2 Decreases H2AX Ubiquitination and Inhibits Cell Transformation

Abstract: Histone H2AX is a histone H2A variant that is ubiquitously expressed throughout the genome. It plays a key role in the cellular response to DNA damage and has been designated as the histone guardian of the genome. Histone H2AX deficiency decreases genomic stability and increases tumor susceptibility of normal cells and tissues. However, the role of histone H2AX phosphorylation in malignant transformation and cancer development is not totally clear. Herein, we found that ribosomal S6 kinase 2 (RSK2) directly ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Deficiency of histone H2AX decreases genomic stability and increases tumor susceptibility of normal cells and tissues, suggesting that it might act as a tumor suppressor [27,28] . Increasing evidence, along with our present results show that the function of H2AX involved in regulation of apoptosis is mediated by its C-terminal phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of histone H2AX decreases genomic stability and increases tumor susceptibility of normal cells and tissues, suggesting that it might act as a tumor suppressor [27,28] . Increasing evidence, along with our present results show that the function of H2AX involved in regulation of apoptosis is mediated by its C-terminal phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that S139P is necessary but not sufficient to dictate both cellular outcomes and that other unique modifications or events that function in conjunction with S139P must occur in a pathway-specific manner. A recent study by Zhu et al investigated the role of H2AX Ser139 in epidermal growth factor (EGF)-mediated transformation of cells (140). They observed that EGF treatment resulted in phosphorylation of Ser139 and Ser16 of H2AX; they also identified ribosomal S6 kinase 2 (RSK2) as the enzyme responsible for these modifications (140).…”
Section: Histone H2amentioning
confidence: 99%
“…A recent study by Zhu et al investigated the role of H2AX Ser139 in epidermal growth factor (EGF)-mediated transformation of cells (140). They observed that EGF treatment resulted in phosphorylation of Ser139 and Ser16 of H2AX; they also identified ribosomal S6 kinase 2 (RSK2) as the enzyme responsible for these modifications (140). Their study revealed that EGF-dependent phosphorylation of Ser139 and Ser16 results in stabilization of H2AX and a decrease in AP1 transactivation.…”
Section: Histone H2amentioning
confidence: 99%
“…A recent study showed that MCPH1, a protein associated with DNA damage response, interacts with di-phosphorylated (S139/Y142ph) H2A.X [103]. Finally, recent data showed that H2A.X S16 can also be phosphorylated, and this modification results in decreased H2A.X ubiquitylation and cell transformation [104].…”
Section: H2ax and Dna Damage Repairmentioning
confidence: 99%